Sistem Pengukuran Kinerja dan Pengaturan Keorganisasian yang Ideal bagi Unit Kerja Pengelola Risiko Kredit, Studi Kasus PT Bank Mega, Tbk - , Andina ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research will normatively reveal how credit analyst unit is set normatively in terms of its organization, and how its performance measurement system is developed in order to know its effectiveness, to mitigate credit risk of a bank which might cause systemic risk in the country. Research is done qualitatively, using case study technique in credit analyst unit in PT Bank Mega, Tbk, and content analysis to analyze relevant data gained from internal and external sources. Data analysis shows that in banking organization, credit analyst unit should not be put under the same supervision with business unit to avoid intervention and conflict of interest. Credit analyst unitâs function and authority should stay independent in order to let biases affect decision making in terms of producing credit recommendation. Thus, credit analyst unitâs performance measurement system is build based on four perspectives of Balanced Scorecard as follows, (1) Financial, which is problem loan cost minimization, (2) Customer, which is credit analyst unitâs strategic constituent satisfaction, (3) Internal Process, which is credit analysis process acceleration, and (4) Learning and Growth, which is credit analyst personal competence enhancement.